Analisis Produktivitas Alat Berat Pada Pekerjaan Timbunan untuk Proyek Infrastruktur Irigasi - Muhammad Alfie Dhiyaulhaq Daffa; Athaya Zhafirah (Institut Teknologi Garut, 2026)
This study analyzed the productivity of heavy equipment (Dump Truck, Excavator, and Vibro Roller) on embankment works for irrigation modernization project. Using quantitative methods, field data were compared with theoretical calculations to evaluate productivity, cycle time, and operating costs. Results show that proper machine selection increases efficiency by up to 20%, with significant cost savings. The findings provide guidance for resource optimization on infrastructure projects.